2002
DOI: 10.1021/cm011277g
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Sintering of the Thorium Phosphate-Diphosphate. Study of Physical, Thermal, and Thermomechanical Properties and Chemical Durability during Leaching Tests

Abstract: Taking into account some attractive properties of the thorium phosphate−diphosphate (Th4(PO4)4P2O7), called TPD, we focused our research on its potential use as a ceramic for the long term storage of some radionuclides including trivalent and tetravalent actinides. In this objective, we already investigated with success several ways of preparation of the pure TPD and solid solutions with tetravalent actinides either by wet or dry chemical methods. In the field of nuclear applications and considering handling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 42 publications
5
48
0
1
Order By: Relevance
“…Sintered pellets were prepared using a two-step procedure (involving an uniaxial pressing at room temperature followed by a heat treatment at 1250°C). For all the samples, the apparent and effective relative densities reached 90-95% and 94-99% of the value calculated from XRD data, respectively [24]. Leaching tests achieved in various solutions demonstrated that both powdered and sintered samples doped, or not, with tetravalent actinides, exhibit a strong resistance to aqueous corrosion [21,25,26].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Sintered pellets were prepared using a two-step procedure (involving an uniaxial pressing at room temperature followed by a heat treatment at 1250°C). For all the samples, the apparent and effective relative densities reached 90-95% and 94-99% of the value calculated from XRD data, respectively [24]. Leaching tests achieved in various solutions demonstrated that both powdered and sintered samples doped, or not, with tetravalent actinides, exhibit a strong resistance to aqueous corrosion [21,25,26].…”
Section: Introductionmentioning
confidence: 78%
“…b-TPD appears as a promising material for the immobilization of tetravalent actinides [14,22,24]. Actually, it was demonstrated that b-TPD can incorporate large amounts of tetravalent uranium (up to 47.6 wt%), neptunium (33.2 wt%) or plutonium (26.1 wt%) by substitution of thorium [17][18][19][20]23].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and characterization of thorium and uranium phosphate compounds such as U(UO 2 )(PO 4 ) 2 , Th 4 (-PO 4 ) 4 P 2 O 7 (thorium phosphate-diphosphate) and ThO 2 -MO 2 -P 2 O 5 (M = U, Ce, Zr, Pu) was a popular focus of study in the 1990s [9][10][11][12][13]. These phosphate compounds contain uranium or thorium atoms, indicating that phosphate and actinide atoms possess a strong binding ability.…”
Section: Introductionmentioning
confidence: 99%
“…Several phosphates such as Zr 2 O(PO 4 ) 2 , ZrP 2 O 7 and Th 4 (PO 4 ) 4 P 2 O 7 have been studied as potential substitutes for immobilization and long-term storage of uranium [18]. Phosphates, especially rare earth phosphates, have poor solubility, strong irradiation resistance, excellent thermal stability, good binding ability with actinide elements, and high adsorption capability on actinide elements and heavy metals [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. For this reason, rare earth phosphates as adsorbents are expected to play a significant role in the safety of underground radwaste repositories due their potential use for an engineered containment barrier.…”
Section: Introductionmentioning
confidence: 99%